If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 41 = 12x + -103 Reorder the terms: 41 + 3x = 12x + -103 Reorder the terms: 41 + 3x = -103 + 12x Solving 41 + 3x = -103 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 41 + 3x + -12x = -103 + 12x + -12x Combine like terms: 3x + -12x = -9x 41 + -9x = -103 + 12x + -12x Combine like terms: 12x + -12x = 0 41 + -9x = -103 + 0 41 + -9x = -103 Add '-41' to each side of the equation. 41 + -41 + -9x = -103 + -41 Combine like terms: 41 + -41 = 0 0 + -9x = -103 + -41 -9x = -103 + -41 Combine like terms: -103 + -41 = -144 -9x = -144 Divide each side by '-9'. x = 16 Simplifying x = 16
| 2/10-8/100/2/10 | | 42=y+12 | | 30=-16t^2+30t | | -7(4)=n | | 10x-100= | | (2r^-1s^2t^0)^-2/2rs | | 13-(-9)=x | | 9x^4-9x^3-225x^2-225x=0 | | 2.1x+5=49.10 | | -3(4x+3)+2(5x-8)= | | 24=2t+5t^2 | | -2(7w-7)+w=5(w+4) | | (8b-10)-2(6-3b)= | | 1.29x+21+0.99=15 | | (4p-8)+(6p-7)= | | 2x+7-5=-17 | | 18x+1=15x+10 | | Sin(x)/2x | | 8-2(3y+5)= | | x^2-4x+70=0 | | -y+15=241 | | 6f+3(f+9)= | | 5x-(4)-2y+z=0 | | 3(u-9)=-54 | | (3x×sinx)/2x=sin40 | | -2(y+4)+4(2y+5)= | | 7(x+2)-6= | | 4n=2*12 | | x^2+y^2=3x-4y | | -3(y+5)-2y= | | 20=-5/2u | | -(x+1)-1= |